Comparison of serum copper, zinc, calcium, and magnesium levels in preeclamptic and healthy pregnant women - Kumru, S; Aydin, S; Simsek, M; Şahin, Kazım; Yaman, M; Ay, G (Springernature, 2003)
Deficient or excessive levels of blood trace elements can be an adverse factor in human and animal pregnancy The aim of this study was to investigate possible differences in the levels of serum magnesium, calcium, copper, and zinc in preeclamptic and healthy pregnant women. Samples were collected from 30 preeclamptic (PE) and 30 healthy pregnant (HP) women. The serum copper concentration was significantly lower in the PE group by 68% (p<0.0001) when compared to the healthy controls. The serum zinc and calcium were 43% and 10% lower in the PE women, respectively (both with p<0.0001), whereas the magnesium concentration showed nonsignificant differences between the two groups. Measurement of these elements may be useful for the early diagnosis of a preeclamptic condition.
Keywords: preeclampsia; calcium; magnesium; copper; zinc